The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.26858/jds.v7i3.11874
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness Of Scientific Approach With Open-Ended Problem Based Learning Worksheet Viewed From Learning Achievement, Creative Thinking Ability, Interest, And Mathematics Self-Efficacy

Abstract: This study aimed to describe the effectiveness and differences of scientific approach with open-ended problem based learning worksheet and scientific approach. The population in this study was students of class VII of SMP Negeri 17 Pamulang, South Tangerang. The sample of this study was determined randomly. They were two classes and the results were VII.3 and VII.4. To determine the effectiveness, one sample t-test was used. To discover the difference of effectiveness, MANOVA (Hotteling's Trace) test was used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
1
3
0
8
Order By: Relevance
“…According to Bayraktar (2001), this kind of phenomenon implies the Hawthorne effect that firsttime PBL has a significant impact on students' creative mathematical thinking, perhaps because of its novelty. Similar results were also reported by Masitoh and Prasetyawan (2019) that PBL had a big impact when it was first implemented. The result of is 55,683 > is 12.59 with a significance level of 0.05, meaning that there are significant differences between groups in the aspects of the research year.…”
Section: Findings and Discussionsupporting
confidence: 89%
“…According to Bayraktar (2001), this kind of phenomenon implies the Hawthorne effect that firsttime PBL has a significant impact on students' creative mathematical thinking, perhaps because of its novelty. Similar results were also reported by Masitoh and Prasetyawan (2019) that PBL had a big impact when it was first implemented. The result of is 55,683 > is 12.59 with a significance level of 0.05, meaning that there are significant differences between groups in the aspects of the research year.…”
Section: Findings and Discussionsupporting
confidence: 89%
“…Pada aspek tampilan pemilihan warna background, cover, video pembelajaran dan gambar yang disajikan pada E-LKPD interaktif dengan model project based learning sudah jelas. Kejelasan yang disajikan akan membuat siswa tertarik menggunakannya (Masitoh & Prasetyawan, 2020;Servitri & Trisnawaty, 2018). Dilihat dari aspek penggunaan E-LKPD interaktif mudah digunakan, mudah diakses dan alur penggunaan beserta fitur-fitur pada E-LKPD interaktif sudah jelas.…”
Section: Pembahasanunclassified
“…This approach also focuses on progress and development rather than the product. Previous research found that scientific approach could encourage teachers to act as facilitators (Djaelani, 2019;Hariyatmi et al, 2019;Masitoh & Prasetyawan, 2020); Saryantono & Nurdiana, 2018;Setyarini, 2018;Wirapathi et al, 2019;Yanto, 2019). Thus, the learning targets were the learners.…”
Section: Discussionmentioning
confidence: 99%